Abiotic and Biotic Stress in Plants 2019
DOI: 10.5772/intechopen.83562
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology a Potential Tool to Mitigate Abiotic Stress in Crop Plants

Abstract: The response of plants to abiotic stress is complex and involves changes in their morphology, physiology and metabolism. A number of strategies are being followed to enhance the tolerance of abiotic stress conditions, including the development of genetically-engineered varieties containing various gene constructs believed to enhance the performance under stress conditions. Nanotechnology is a versatile field and has found application in almost all the existing fields of science. The application of nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…At first, NPs choose lateral root synapse to enter into the plant rhizosphere and outreach towards xylem via cortex and then pericycle [194]. However, their association with plants takes place on the basis of some biochemical activities which may activate not only the transport of ions into the cell but also reacts with -SH and -COOH groups, and modifies protein levels in the plant cells [195]. Additionally, NPs are able to form a network with the transporters present in the membrane of plant root cells to fetch inside the plants [196,197].…”
Section: Biochemical Mechanism Of Metal/metalloid-based Nanoparticles To Mitigate Abiotic Stressesmentioning
confidence: 99%
“…At first, NPs choose lateral root synapse to enter into the plant rhizosphere and outreach towards xylem via cortex and then pericycle [194]. However, their association with plants takes place on the basis of some biochemical activities which may activate not only the transport of ions into the cell but also reacts with -SH and -COOH groups, and modifies protein levels in the plant cells [195]. Additionally, NPs are able to form a network with the transporters present in the membrane of plant root cells to fetch inside the plants [196,197].…”
Section: Biochemical Mechanism Of Metal/metalloid-based Nanoparticles To Mitigate Abiotic Stressesmentioning
confidence: 99%
“…Nanofertilizers have come up as an important alternative strategy to cope up with drought stress. Among nanoformulations, metal-based nanoformulations have performed great in this area [ 34 , 90 ]. Nano-ZnO treatment improved the drought tolerance of the maize ( Zea mays ) plants by promoting the endogenous synthesis of melatonin which inhibits the accumulation of malondialdehyde and osmolytes in the leaves [ 149 ].…”
Section: Better Efficiency Under Stressesmentioning
confidence: 99%
“…The negative effects of drought stress on lentils ( Lens culinaris Medic.) plants was reduced by the application of silver NPs ( Das and Das, 2019 ). Sun et al (2017) reported Si NPs-assisted delivery of abscisic acid as an effective management strategy to improve drought resistance in Arabidopsis thaliana .…”
Section: Effects Of Nps In Plants Under Drought Stressmentioning
confidence: 99%